Transition-Metal-Catalyzed C–H Arylation Using Organoboron Reagents - Basak, Sumon; Biswas, Jyoti Prasad; Maiti, Debabrata (Synthesis, 2021)
Aryl rings are ubiquitous in the core of numerous natural product and industrially important molecules and thus their facile synthesis is of major interest in the scientific community and industry. Although multiple strategies enable access to these skeletons, metal-catalyzed C–H activation is promising due to its remarkable efficiency. Commercially available organoboron reagents, a prominent arylating partner in the cross-coupling domain, have also been utilized for direct arylation. Organoborons are bench-stable, inexpensive, and readily available coupling partners that promise regioselectivity, chemodivergence, cost-efficiency, and atom-economy without requiring harsh and forcing conditions. This critical, short review presents a summary of all major studies of arylation using organoborons in transition-metal catalysis since 2005.1 Introduction2 Arylation without Directing Group Assistance2.1 Palladium Catalysis2.2 Iron Catalysis2.3 Gold Catalysis3 Arylation with Directing Group Assistance3.1 Palladium Catalysis3.2 Ruthenium Catalysis3.3 Rhodium Catalysis3.4 Nickel Catalysis3.5 Cobalt Catalysis3.6 Copper Catalysis4 Conclusion
Keywords: transition-metal catalysis; C–H activation; arylation; organoboron; C–H functionalization; heterocycle